Analytical approaches to banking system stability: a study of methods and current state of banks in Kazakhstan (Journal of Economic Research & Business Administration, 2025)
The article presents methods of assessing the sustainable development of the banking system, which are highly relevant today, and the current analysis of indicators of financial stability indicators of second-tier banks of the Republic of Kazakhstan. The article examines various methods of assessing the stability of banking institutions, which play a crucial role in ensuring the stability of the financial system. The main focus is on the analysis of approaches and tools used to assess the financial stability of banks, such as stress testing, analysis of financial ratios and rating systems. A comparative analysis of the methods of stability analysis used in the modern banking sector is provided. The features, strengths and weaknesses, opportunities and risks of the CAMELS, BAKIS, PATROL, SREP methods of banking stability analysis thoroughly examined, along with a theoretical justification of their peculiarities. Additionally, the article conducts an analysis of the current state of commercial banks of the Republic of Kazakhstan using comparative analysis and comprehensive stability assessments to prevent financial crises and maintain public confidence in the banking sector. The authors also highlight the necessity of adapting assessment methods to reflect changes in the global economy and the evolving dynamics of the banking sector.Key words: commercial banks, sustainable development concept, ESG, sustainability assessment, sustainable banks.